Transcription Profiles of Marker Genes Predict The Transdifferentiation Relationship between Eight Types of Liver Cell during Rat Liver Regeneration - Xiaguang Chen; Cunshuan Xu (Cell Journal, 2015)
Objective: To investigate the transdifferentiation relationship between eight types of liver cell during rat liver regeneration (LR). Materials and Methods: 114 healthy Sprague-Dawley (SD) rats were used in this experimental study. Eight types of liver cell were isolated and purified with percoll density gradient centrifugation and immunomagentic bead methods. Marker genes for eight types of cell were obtained by retrieving the relevant references and databases. Expression changes of markers for each cell of the eight cell types were measured using microarray. The relationships between the expression profiles of marker genes and transdifferentiation among liver cells were analyzed using bioinformatics. Liver cell transdifferentiation was predicted by comparing expression profiles of marker genes in different liver cells. Results: During LR hepatocytes (HCs) not only express hepatic oval cells (HOC) markers (including PROM1, KRT14 and LY6E), but also express biliary epithelial cell (BEC) markers (including KRT7 and KRT19); BECs express both HOC markers (including GABRP, PCNA and THY1) and HC markers such as CPS1, TAT, KRT8 and KRT18; both HC markers (KRT18, KRT8 and WT1) and BEC markers (KRT7 and KRT19) were detected in HOCs. Additionally, some HC markers were also significantly upregulated in hepatic stellate cells ( HSCs), sinusoidal endothelial cells (SECs) , Kupffer cells (KCs) and dendritic cells (DCs), mainly at 6-72 hours post partial hepatectomy (PH). Conclusion: Our findings indicate that there is a mutual transdifferentiation relationship between HC, BEC and HOC during LR, and a tendency for HSCs, SECs, KCs and DCs to transdifferentiate into HCs.